Tool for Performance Appraisal - Assudani, Kajol; Ramchandani, Nilesh; Balani, Nisha (International Journal of Computer Sciences and Engineering, 2025)
In the corporate world people have different qualities and attributes to show for which there is a need of assessment. Employees are needed to be given the due credit for how the perform at the site of the job [2]. Older methods include a paper consisting of the employee credentials along with a fixed set of qualities. This becomes the basis on which the higher authorities get to take the decisions on a particular employee. As the medium of on paper appraisal becomes obsolete our software provides a portal to appraise an employee with a dynamic system to appraise and assess them in a fairer and an advanced manner [5]. AppraiSyst is basically a web app which can inherently be used by firms and teams to assess the employees on their own scale with enough dynamic components to suit any work environment.